2016
DOI: 10.1186/s11689-016-9172-7
|View full text |Cite
|
Sign up to set email alerts
|

Typical visual search performance and atypical gaze behaviors in response to faces in Williams syndrome

Abstract: BackgroundEvidence indicates that individuals with Williams syndrome (WS) exhibit atypical attentional characteristics when viewing faces. However, the dynamics of visual attention captured by faces remain unclear, especially when explicit attentional forces are present. To clarify this, we introduced a visual search paradigm and assessed how the relative strength of visual attention captured by a face and explicit attentional control changes as search progresses.MethodsParticipants (WS and controls) searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
2
15
3
Order By: Relevance
“…In our previous study (Hirai et al . in preparation), we found a significant negative correlation between fixation–duration proportion for upright faces and RCPM scores, but no significant correlation with chronological age. In contrast to those findings, we did not find a significant correlation between the fixation–duration proportion for inverted faces and RCPM scores in the current study.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…In our previous study (Hirai et al . in preparation), we found a significant negative correlation between fixation–duration proportion for upright faces and RCPM scores, but no significant correlation with chronological age. In contrast to those findings, we did not find a significant correlation between the fixation–duration proportion for inverted faces and RCPM scores in the current study.…”
Section: Discussioncontrasting
confidence: 46%
“…The current finding contrasts with our previous findings regarding the atypical attention towards upright faces in individuals with WS (Hirai et al . in preparation). Here, we did not find that WS individuals had atypical gaze responses towards the inverted faces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We also observed that the looking time proportion for face stimuli was significantly longer than that for objects across all ages, consistent with previous studies that utilized an identical experimental paradigm (Hirai, et al, 2016a, 2016b). Therefore, the looking time proportion reflected the attentional profile at the later period of searching and did not differ across groups.…”
Section: Discussionsupporting
confidence: 91%